Edukasi Pencatatan Keuangan dan Kas Hariansebagai Upaya Meningkatkan Kepatuhan Pajak pada UMKM Pabrik Batu Bata Cahaya Rizki: Pengabdian - Ahmad Syuheri; Didik Setiawan; Yudi Anggoro; Risda Sawatun (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Community service activities with the theme "Education on Financial Recording and Tax Compliance for Cahaya Rizki Brick Factory MSMEs" have been implemented well and have had a positive impact on increasing financial literacy and tax awareness of MSME actors. This activity aims to help business actors understand the importance of regular financial recording and tax obligations in accordance with the provisions of applicable laws and regulations, especially PP No. 23 of 2018 concerning Income Tax on Income from Businesses Received or Obtained by Taxpayers with Certain Gross Turnover. Through activities in the form of training, daily cash book filling simulations, interactive discussions, and assistance in recording practices, participants gained a practical understanding of how to prepare simple financial reports and calculate 0.5% Final Income Tax. The results of the activity showed an increase in the ability of MSME actors to separate personal and business finances, record transactions systematically, and understand their tax obligations as business actors. In addition, this activity opens up opportunities for MSME actors to implement a more orderly and transparent financial system as a basis for business decision making.